Perencanaan Sistem Penyediaan Air Bersih Mukti Desa Tenjowaringin Kabupaten Tasikmalaya - Desty Rahmawati Kusumah; Sulwan Permana; Anjas Ninda Hantari (Institut Teknologi Garut, 2023)
Clean water is the main source for society. However, not all areas have sufficient availability of clean water, for example Pangkalan Village and Pasir Mukti Village which are located in Tenjowaringin Village. In this research, planning for the availability of clean water was carried out for the people of Pangkalan village and Pasir Mukti village. The spring used in the planning was the Cipeuti spring, the water source of which had not been utilized at all. The method used to determine the amount of discharge is the volumethic method by collecting spring water, then the water is raised to the distribution reservoir using a pump, then the water is distributed using a gravity system. However, the method that will later be used for distribution of clean water is planned using the help of Epanet 2.2 software. The results of the analysis of water needs until the 2033 plan year showed that the population was 474 people using the geometric method, for a water discharge of 13,140 lt/day (0.16 lt/sec) with Cipeuti water availability until 2033, namely 0.17 lt/sec. The results of the calculations show that the availability of clean water in Cipeuti can meet the water needs of the people of Pangkalan village and Pasir Mukti village. For the dimensions of the reservoir used, namely 2.5 m x 2.5 m x 3 m and the dimensions of the planned reservoir are 2.5 m x 2.5 m x 3.5 m, the type of pipe used is HDPE pipe, where the value of the pipe coefficient uses Hazen Williams values ”‹”‹which will later be applied in the Epanet 2.2 application for pipe distribution.